Efficient decoding of permutation codes obtained from distance preserving maps - Chee, Yeow Meng (2013)
We study the decoding of permutation codes obtained from distance preserving maps and distance increasing maps from Hamming space. We provide efficient algorithms for estimating the q-ary digits of the Hamming space so that decoding can be performed in the Hamming space.